Safety and Accuracy of Endovascular Aneurysm Repair Without Pre-operative and Intra-operative Contrast Agent. Issue 3 (March 2015) - Kaladji, A.; Dumenil, A.; Mahé, G.; Castro, M.; Cardon, A.; Lucas, A.; Haigron, P.
<x xml:space="preserve">Abstract</x> Background Severe chronic kidney disease is a major limitation for endovascular aortic aneurysm repair (EVAR). The aim of this study is to assess the safety and accuracy of fusion imaging, when performing EVAR in the absence of pre- and intra-operative contrast agents. Methods From October 2013 to February 2014, every patient requiring EVAR and presenting with severe chronic renal impairment underwent a specific pre-operative imaging assessment, based on a non-enhanced CT scan. Centrelines were manually extracted and key points were placed at the landing zones. In house software makes it possible to artificially enhance the contrast between vascular structures and the surrounding tissue, by increasing the values attributed to the vascular structure voxels (500 Hounsfield units). EVAR was performed in a hybrid room (Zeego, Siemens), and the artificially enhanced CT scan was used for the construction of fusion imaging. The 3D vascular volume, together with the centrelines and key points, was overlaid onto the 2D live fluoroscopic image. Results Six patients (mean age 77.1 years) were treated by EVAR (5 abdominal aneurysms and 1 thoracic aneurysm), using fusion imaging without a contrast agent. The median pre-operative estimated glomerular filtration rate (eGFR) was 17.5 mL/min/1.73 m2. No contrast was used during the procedure. No intra-operative endoleak was observed on the duplex scan. No deterioration was observed in the eGFR at 1 week (eGFR = 21.7, p = .49), nor at 1 month follow up (eGFR = 21, p = .28). The stent graft positioning error was assessed in terms of the difference between the effective and planned landing zones, measured on pre- and post-operative CT scans. The mean error was 1.3 mm at the proximal landing zone, and 6.5 mm at the distal landing zone. Conclusion EVAR without the use of pre-operative and intra-operative contrast agents appears to be safe and accurate for patients with severe chronic kidney disease.